(untitled) (Journal of NELTA, 2016)
This research examines how realistic EFL learners are in making judgement of their EFL reading comprehension performance. Appraisal confidence and appraisal calibration have been used as frameworks in this study. Appraisal confidence refers to the degree to which learners believe that their answer to a test item is correct or appropriate. It is expressed in percentage terms (e.g., 0%, 25%, 50%, 75%, or 100%). Appraisal calibration examines the accuracy of learners’ appraisal confidence. Being realistic about accuracy in performance (i.e. appraisal calibration) is considered to be an indicator of effective learning. However, despite its importance, appraisal confidence and appraisal calibration has gained little attention especially in EFL reading. In order to minimize this knowledge gap, this study examined the appraisal confidence and appraisal calibration of eighty-five EFL students studying Master of Education (M. Ed) with specialization in English in Tribhuvan University. An EFL reading comprehension test specifically designed for the study and appraisal confidence rating scales incorporated in the same EFL reading comprehension test were used as the tools for data collection. The findings of the study show that the students in general were not well calibrated. However, high performers were better calibrated than the low performers. The implications of the study for teaching and suggestions for further research are discussed. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page:61-73